203 TRANSITIONS TO LONG-TERM CARE: EXPERIENCE OF A COHORT OF COMMUNITY-DWELLING OLDER ADULTS RECEIVING INTEGRATED CARE. (25th October 2022) - Mahon, CM; Dunne, A; Garcia, R; Martin, R; Kennelly, SM
Abstract: Background: Data from the Nursing Home support scheme 2018 (NHSS) shows the majority of applications to the NHSS come from acute hospitals (44%) followed by referrals from the community (38%). We examined this transition in a cohort of community dwelling older adults to assess how many transition from home to nursing home and, when admission to nursing home from hospital occurred, the indications for same. Methods: Retrospective examination of Integrated Care Team (ICT) and Acute Hospital data from 2019 in respect of a cohort of older adults. Transitions in care to nursing home including residence at time of admission, last acute hospital presentation prior to nursing home admission and commencement of NHSS application recorded. Results: 319 patients referred to the integrated care service in 2019, average age 81 and 58% female, predominantly from outpatient clinics in the Medicine for the Older Person's service. 47 patients had moved to nursing home; within this cohort 14 (29.7%) transitioned from home, 28 (59.6%) transitioning after acute hospital admission. Main reasons for presentation to hospital were: Intercurrent acute illness (n=11); Falls (n=6); progression of dementia (n=4). Fair Deal application commenced in community by ICT in 20 of the 47 (42.5%) patients including 8 of 28 patients (28.5%) admitted to hospital prior to moving to nursing home. Conclusion: This preliminary evaluation highlights the importance of advance care planning in this population when acute hospital admissions can be difficult to predict. Involvement of the ICT can help this transition and lead to shorter hospital stays.